Comparative studies of chloride permeability, conductivity and salt-ponding tests of concrete containing different admixtures. (15th July 2009) - Uchoa, Silvia B.; Ray, Indrajit; Davalos, Julio F.; Tonholo, Josealdo
Concrete modified with various chemical and mineral admixtures are gaining popularity as construction materials, but inclusion of admixtures raises questions about the validity of standard tests of transport properties and conductivity. To explore most representative tests, the present study has evaluated and compared transport properties by several methods: standard rapid chloride permeability test (RCPT), modified RCPT, electrical conductivity, electrochemical impedance spectroscopy (EIS), and salt-ponding tests. Three normal concretes and nine high-performance concretes including different combinations of mineral admixtures were investigated. Results show that the effects of heat generation in RCPT cells were dependent on the types and combinations of mineral admixtures, and that pore solutions had definite effects in RCPT results. The relatively expensive and difficult test of EIS can be replaced by one-minute RCPT and conductivity meter test. The correlations between salt-ponding tests and various RCPTs were found to be weak due to different mechanisms involved.